Relevance of Muhammad Rasyid Ridha's Concept of Women's Education to the Education System at Ma'had Al-Jami'ah - Erina Dwi Parawati; Taufikin Taufikin (Al Hikmah: Journal of Education, 2025)
This study analyzes the concept of women's education based on Muhammad Rashid Ridha's perspective and its relevance to the education system at Ma'had Al-Jami'ah IAIN Kudus. Using a descriptive qualitative approach, this study explores Ridha's educational values that emphasize gender equality in Islam, the integration of religious and general knowledge, and the formation of women's character as educators of the next generation. The results show that the education system in Ma'had Al-Jami'ah implements these principles through an inclusive curriculum while maintaining moral and religious values. However, there are adaptations to meet modern needs, such as English language teaching and extracurricular activities. This study confirms the relevance of Ridha's views in empowering women through holistic education by Islamic values.